A study on conflicts during an interdisciplinary capstone design experience. (1st January 2014) - Harper, Steven R.; Nagel, Robert L.
When teams are formed there is often conflict that arises. However, not all conflict is detrimental to the final deliverables of the team. Conversely, extreme presence of conflict or the wrong type of conflict is counterproductive. We studied two types of new teams. One type of new team was composed solely of students majoring in engineering, while the second type was composed of students majoring in engineering and students majoring in management. Models were fit with a superset of variables to determine the causes of task, relational, and process conflict. Our overarching goal is to understand the factors which each of the student groups perceive to cause conflict such that we can tailor our instruction toward helping the two different groups to work together as a successful project team. Among the findings are that the variables influencing the types of conflict between the two types of students are distinct.